1998
DOI: 10.1001/archinte.158.15.1633
|View full text |Cite|
|
Sign up to set email alerts
|

Physical Activity Improves the Metabolic Risk Profiles in Men and Women

Abstract: Sustained high levels and change from sedentary to higher levels of physical activity relative to sedentary men and women improved the metabolic risk profiles in both sexes. The differences observed are sufficiently large to have a beneficial effect in the prevention of certain chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
77
2
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 61 publications
15
77
2
4
Order By: Relevance
“…Moreover, the accuracy of the levels of recreational activity reported on the questionnaire has been validated and the level of recreational activity correlates positively with physical fitness. [55][56][57] The findings in our study that women who were sedentary in their leisure time had a higher BMI and a significant dyslipidemia relative to those who were active (p Ͻ 0.05 for higher BMI, serum LDL/HDL ratio and serum triglycerides in inactive vs. active, age adjusted; results not shown) strengthen the validity of our assessment.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, the accuracy of the levels of recreational activity reported on the questionnaire has been validated and the level of recreational activity correlates positively with physical fitness. [55][56][57] The findings in our study that women who were sedentary in their leisure time had a higher BMI and a significant dyslipidemia relative to those who were active (p Ͻ 0.05 for higher BMI, serum LDL/HDL ratio and serum triglycerides in inactive vs. active, age adjusted; results not shown) strengthen the validity of our assessment.…”
Section: Discussionsupporting
confidence: 59%
“…Benefits to the circulatory system include influences on the lipoprotein metabolism, inflammatory markers, endothelial function and insulin resistance. [39][40][41][42][43][44][45][46] Is physical activity important among those who lose weight? Our study showed that leisure time physical activity had protective effect on all-cause mortality, which is in line with numerous other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent physical activity may also act through hormonal mechanisms by continuing to impact ovarian hormone levels among premenopausal women, may directly lower estrogen levels, 34 or may alter circulating estrogen levels of postmenopausal women indirectly 9 by lowering BMI or maintaining weight among postmenopausal women. [35][36][37][38] Other mechanisms that have been proposed for the protective effect of exercise on invasive breast carcinoma risk, such as alterations in immune response 39,40 and increased insulin sensitivity, 36,41 may also account for the decrease in risk of BCIS. The insulin sensitivity hypothesis is related to the previously mentioned hormonal pathway.…”
Section: Discussionmentioning
confidence: 99%